Maternal-child health interdisciplinary aspects within the perspective of global health - Groß, Uwe; Wydra, Kerstin (Universitätsverlag Göttingen, 2013)
Maternal-Child Health is one of the greatest challenges the world has to cope with today. Every year, thousands of women, newborns and children die unnecessarily, particularly in resource-poor settings. There is a great disparity caused by food insecurity and hunger, environmental health risks, sanitation challenges, cultural barriers and non-accessibility to diagnosis and treatment. "Maternal-Child Health: Interdisciplinary Aspects within the Perspective of Global Health" addresses these issues. The contributions of this book are based on the ONE HEALTH concept by focusing on infectious and non-communicable diseases and to present interdisciplinary views from more than 60 authors who come from 14 countries. The aim is to shape our understanding on Maternal-Child Health Solutions by looking at > agricultural and environmental > economic, social and theological > biomedical and nutritional > clinical human and veterinary as well as > epidemiology and > public health expertise. The Göttingen International Health Network is corresponding to a variety of different geographic regions and programs to improve global health perspective and health of the most vulnerable: mothers and their children.